Práticas pedagógicas transformadoras escolares na Educação de Jovens e Adultos: contribuições de revistas da América Latina e Caribe - Leal, Igor Gabriel (2021)
This bibliographic research has as central theme educational transformative school practices in Youth and Adult Education (EJA). In this sense, the general objective of this work is to: identify and analyze school pedagogical practices in Latin America and the Caribbean, in view of the contributions of the elements that compose them to the offer of transformative practices for young people and adults. To do so, we start from a theoretical framework based on Paulo Freire, as well as on other authors who relate in a coherent way with this main framework. Following the theoretical contributions of the bibliographic research, this research investigated 55 articles from four different magazines focused on Youth and Adult Education and indexed in the Latindex catalog, in the search to establish whether and how the practices described in these articles contribute to overcoming exclusionary situations. The results indicate that the analyzed practices contribute to overcoming exclusionary situations related to: Human and Civil Rights; Illiteracy; Conflicts of knowledge; Methodological conflicts; Organizational and Physical Conflicts. Such practices can, therefore, be considered transformative when articulating with strategies that relate to the Freirean concepts presented in the theoretical framework of this research. We also highlight articles analyzed that did not seek to intervene in any exclusionary situation.